Establishing phase definitions for jump and drop landings and an exploratory assessment of performance-related metrics to monitor during testing - Harry, J. R.; Simms, A.; Hite, M. (The Journal of Strength and Conditioning Research, 2024)
Landing is a common task performed in research, physical training, and competitive sporting scenarios. However, few have attempted to explore landing mechanics beyond its hypothesized link to injury potential, which ignores the key performance qualities that contribute to performance, or how quickly a landing can be completed. This is because a lack of (a) established landing phases from which important performance and injury risk metrics can be extracted and (b) metrics known to have a correlation with performance. As such, this article had 2 purposes. The first purpose was to use force platform data to identify easily extractable and understandable landing phases that contain metrics linked to both task performance and overuse injury potential. The second purpose was to explore performance-related metrics to monitor during testing. Both purposes were pursued using force platform data for the landing portion of 270 jump-landing trials performed by a sample of 14 NCAA Division 1 men's basketball players (1.98 ± 0.07 m; 94.73 ± 8.01 kg). The proposed phases can separate both jump-landing and drop-landing tasks into loading, attenuation, and control phases that consider the way vertical ground reaction force (GRF) is purposefully manipulated by the athlete, which current phase definitions fail to consider. For the second purpose, Pearson`s correlation coefficients, the corresponding statistical probabilities (a = 0.05), and a standardized strength interpretation scale for correlation coefficients (0 < trivial = 0.1 < small = 0.3 < moderate = 0.5 < large = 0.7 < very large) were used for both the group average (i.e., all individual averages pooled together) and individual data (i.e., each individual's trials pooled together). Results revealed that landing time, attenuation phase time, average vertical GRF during landing, average vertical GRF during the attenuation phase, average vertical GRF during the control phase, vertical GRF attenuation rate, and the amortization GRF (i.e., GRF at zero velocity) significantly correlated with landing performance, defined as the ratio of landing height and landing time (R = ± 0.58; p < 0.05), such that favorable changes in those metrics were associated with better performance. This work provides practitioners with 2 abilities. First, practitioners currently assess jump capacity using jump-landing tests (e.g., countermovement jump) with an analysis strategy that makes use of landing data. Second, this work provides preliminary data to guide others when initially exploring landing test results before identifying metrics chosen for their own analysis.